Existing production and marketing system of fodder under Meherpur district as livelihood activity - Roy, BK; Sarker, NR; Alam, MK; Huque, KS (Bangladesh Journal of Livestock Research, 2016)
An investigation was carried out with the objectives to determine the existing production and marketing system of fodder as a livelihood activity of farmers under Meherpur district. For this, a purposive survey was conducted covering three Upazilas of Meherpur district namely, Meherpur Sadar, Gangni and Mujibnagar. Before conducting the survey, a Focus Group Discussion (FGD) was arranged and it was identified that there were three stakeholders involved under these areas: fodder producers, middlemen and users of fodder. On the basis of the findings of FGD, a survey was conducted through a pre-tested structured questionnaire as per objectives of the survey. Data were collected randomly from 33 Napier producers, 18 middlemen and 64 fodder users. Survey results indicated that, the average number of cattle and goat per household was 2.12 and 3.19, respectively, while on the other hand none of the farmers under the study areas reared sheep. Sharing of major household income implied that, majority of the fodder producers (72.72%) depended on their livelihood on Napier production and about 83.33% middlemen depends their livelihood on fodder marketing. However, the major sources of income of dairy keepers were business (39.06%), fodder production (20.31%) and agriculture (12.50%). The annual total biomass production of Napier per hectare was 314.48 metric tons. About 45% producers sold green Napier grass in the market, 30% supply directly to middlemen and the rest of 25% farmers marketed their produces directly in market and to middlemen. The prices of a bundle of Napier grass were varied from Tk. 3.00-4.00 to 5.00-6.00, respectively during summer and winter. The total cost, gross income and net profits for Napier production were Tk. 2,37,934.00, Tk. 4,71,723.00 and Tk. 2,33,789.00 per hectare per year, respectively. The benefit cost ratio (BCR) for Napier cultivation was 1.98:1. It can be concluded that fodder production and marketing system in Meherpur district is a profitable enterprises and all the stakeholders under this production and marketing system are getting monetary benefits. Bangladesh J. of Livestock Res. 19(1-2): 24-32, Jan-Dec 2012